(untitled) (International Journal of Physiotherapy, 2025)
Background: Kathak, a classical Indian dance form, involves intricate footwork and expressive movements that often result in a pronated foot posture among female dancers. This study investigates the effectiveness of exercise interventions in correcting pronated foot posture in Kathak dancers. Methods: Sixty female Kathak dancers were divided into two groups: one group participated in both exercise and dance, while the other group engaged in dance only. Foot posture, arch index, and range of motion were evaluated using the Foot Posture Index (FPI), Arch Index (AI), and universal goniometer measurements before and after a 6-week intervention period. Statistical analysis was performed using SPSS. Results: In Group A, significant improvements were observed in FPI scores for both right (p<0.05) and left feet (p<0.05), as well as in Arch Index right: (p<0.05); left: (p<0.05), Range of motion in foot inversion significantly increased in both feet following the exercise program (right: p < 0.05; left: p < 0.05). Group B showed no significant changes in FPI, Arch Index, or range of motion (all p>0.05). Conclusion: Active resisted and stretching exercises effectively improved foot posture, arch angle, and range of motion among Kathak dancers, highlighting the importance of targeted exercise interventions in addressing pronated foot issues associated with dance-specific biomechanical demands.